An evaluation of staff transitioning from a combined adult/child emergency department to a new paediatric emergency department: A qualitative study. Issue 3 (August 2016) - Peeler, Alison; Fulbrook, Paul; Edward, Karen-Leigh; Kinnear, Frances B.
Abstract: Background: Provision of paediatric specific service areas within a hospital servicing both adult and paediatric populations is relatively novel. In Australia this is an emerging model for service delivery that takes into account the specific health needs of paediatric patients. To date, information related to the practice transition required by staff when adopting this model of care is lacking. Such information can contribute to informing service quality and identify staff perceived barriers and enablers during adoption of the model. The potential benefit of such knowledge is the early mitigation of issues and delineation of professional development requirements. The aim of this study was to investigate staff experiences of transitioning from an essentially adult emergency department with minimal paediatric presentations to a new co-located paediatric emergency department. Methods: A qualitative descriptive design was used. Semi-structured interviews were conducted with 18 emergency department staff (10 Nursing, 8 Medical) before and after the opening of the paediatric emergency department. Data were analysed thematically. Results: Five themes emerged from the data analysis, these were: (1) I am really scared that I won't have the skills necessary, (2) Having a good knowledge base helps, (3) Open, transparent communication is definitely the best thing, (4) Personality plays an important role and (5) Perceptions regarding need to separate the services. Conclusions: The findings demonstrated the complexity of the change process and highlights various factors that staff found contributed positively to the change process. These included the need for clear and open communication at all levels, focused educational opportunities, and employment of staff with a positive attitude towards change. Relevance to practice: Clear organisational communication and professional support are central components identified by staff to enable a more successful transition from one type of service to another.